CONTRASTIVE ANALYSIS BETWEEN ENGLISH AND BATAK TOBA LANGUAGE IN QUESTION WORD - Pasaribu, Septiana Hirawati; Tampubolon, Apnes; Sidauruk, Anni; Napitupulu, Selviana (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
This research intends to establish the similarities and differences in question words when using English and the Toba Batak language. It used a qualitative descriptive research design. Documentation techniques were used to collect the data. The researcher used descriptive analysis to analyze the data. The question words in English consist of 9 question words, which are as follows: "What", "Who", "Whose", "When", "Where", "Which", "Why," and "How." And in the Batak Toba language, consists of 11 question words, which are as follows: "Aha", "Ise", "Andigan", "Nandigan", "Dia", "Boasa/Beasa", "Boha", "Piga", "Sadia", "Mahua," and "Marhua." The results show that there are six similarities or equations between English and Toba Batak language in question words. However, there are also six differences between English and Toba Batak language in question words. Question words in English can occur and be put in the beginning and in the middle of interrogative sentence, whereas question words in Batak Toba language can be put in the beginning, in the middle, and at the end of interrogative sentence. English functioning question words similarly to Batak Toba, requesting the following: a person, an object, place, a manner, an activity, time, reason, and possession/ownership.